Keban In the 19th Century: Demographic Structure And Occupations - Çakar, Enver (Fırat University, 2019)
In this study, the demographic structure of Keban in 19th century and the professions that were performed in Keban is investigated by using population records and provincial annuals as sources. Keban, after the Ottoman administration in 1515, has long existed as a district center affiliated to the Sanjak of Çemişgezek. In the 16th and 17th centuries, Keban did not have much importance as before. Therefore had a very small population, but afterwords the population grew rapidly with the start of the mining activities from the beginning of the 18th century, and the town population reached 1023 households (estimated as five thousand people) in 1835. The population in Keban consisted of Greeks and Armenians as well as Muslims. However, the entire non-Muslim population was not a native population which were settled there after the start of mining activities. They were specialized in various professions, mainly in mining. All of the Greeks came from the Black Sea region, especially from another mining region, Gumushane. The Muslims, however, came from the surrounding villages and towns to come to Keban. Again, many Muslim households from the villages close to the town were appointed as the winterers in the mines. Thanks to mining, Keban became a center of attraction since the beginning of the 18th century. Afterwords population in Keban diminished rapidly by the end of the 19th century when mining had lost its importance. Since a significant portion of the population could not find another job to do, they migrated from the town and settled elsewhere. This situation of Keban continued until the middle of the 20th century and it has been improved since 1953 by Etibank when Simli Kurşun Facilities started to operate. This property of the Kebun rotating reverse the growth process by stopping its activities in 1983. Today Keban has one of the largest dams in Turkey and thtough aquaculture (trout) and tourism, Keban nowadays has gained its revival.

Bu çalışmada, nüfus defterleri ve salnameler kaynak olarak kullanılmak su-retiyle, Keban’ın 19. yüzyıldaki demografik yapısı ve burada icra edilen meslekler hakkında bilgi verilmiştir. Keban, 1515 yılında Osmanlı idaresine geçtikten sonra uzun süre Çemişgezek Sancağı’na bağlı bir nahiye merkezi olarak varlığını sürdürmüştür. 16. ve 17. yüzyıllarda fazla bir öneme sahip olmayan ve bu sebeple de oldukça az bir nüfusu barındıran Keban, 18. yüzyılın başlarından itibaren madencilik faaliyetlerinin başlamasıyla birlikte hızla büyümüş ve kasaba nüfusu 1835 yılında 1023 haneye (tahmini olarak beş bin kişi) ulaşmıştır. Keban’daki nüfus, Müslümanların yanı sıra Rum ve Ermenilerden oluşuyordu. Fakat gayrimüslim nüfusun tamamı yerli nüfus olmayıp, madenciliğin başlamasıyla birlikte buraya iskân edilen ve başta madencilik olmak üzere, çeşitli mesleklerde uzmanlaşmış kişilerdi. Rumların hepsi Karadeniz bölgesinden, özellikle de başka bir maden bölgesi olan Gümüşhane’den buraya gelmişlerdi. Müslümanlar ise daha ziyade çevre köylerden ve kasabalardan Keban’a gelerek yerleşmişlerdi. Yine kasabaya yakın olan köylerden birçok Müslüman hane de madenlerde kışlakcı olarak tayin edilmişti. Madencilik sayesinde 18. yüzyılın başlarından itibaren bir cazibe merkezi haline gelen Keban, madenciliğin önemini kaybettiği 19. yüzyılın sonlarına doğru ise hızla sönükleşmiştir. Nüfusun önemli bir kısmı yapacak başka bir iş bulamadığı için kasabadan göç ederek başka yerlere yerleşmiştir. Keban’ın bu vaziyeti 20. yüzyılın ortalarına kadar devam etmiş, Etibank Simli Kurşun Tesisleri’nin faaliyete başladığı 1953 yılından itibaren tekrar gelişme kaydetmiştir. Bu tesislerin 1983  yılında faaliyetlerini durdurmasıyla büyüme süreci tersine dönen Keban, bugün Türkiye’deki en büyük barajlardan birine sahip olması, kültür balıkçılığı (alabalık) ve turizm sayesinde yeniden nisbi bir canlama içerisine girmiştir.
19. YÜZYILDA KEBAN: DEMOGRAFİK YAPI VE MESLEKLER